Canadian Political Economy: An Economic Introduction - Howlett, Michael (Labour / Le Travail, 1991)
The article reviews the book, "Canadian Political Economy: An Economic Introduction," by Paul Phillips.
Keywords: BOOKS -- Reviews; CANADA -- Politics & government; CANADIAN Political Economy: An Economic Introduction (Book); Nonfiction; PHILLIPS, Paul